2009
DOI: 10.1126/science.1176709
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Histone Acetylation in the Nucleus by Sphingosine-1-Phosphate

Abstract: The pleiotropic lipid mediator sphingosine-1-phosphate (S1P) can act intracellularly independently of its cell surface receptors through unknown mechanisms. Sphingosine kinase 2 (SphK2), one of the isoenzymes that generates S1P, was associated with histone H3 and produced S1P that regulated histone acetylation. S1P specifically bound to the histone deacetylases HDAC1 and HDAC2 and inhibited their enzymatic activity, preventing the removal of acetyl groups from lysine residues within histone tails. SphK2 associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
1,062
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 887 publications
(1,099 citation statements)
references
References 21 publications
23
1,062
3
5
Order By: Relevance
“…Perhaps spinster alters the cell death pathway by perturbing the equilibrium of sphingolipids, particularly S1P, in different subcellular compartments. A recent report has revealed S1P epigenetic regulation of gene expression through direct intracellular interaction with histone deacetylases (HDACs) (Hait et al, 2009). Through this mechanism, perhaps increasing intracellular S1P levels alters gene expression, which ultimately leads to elevated translation of muscle proteins, such as Projectin, which then reduces muscle wasting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps spinster alters the cell death pathway by perturbing the equilibrium of sphingolipids, particularly S1P, in different subcellular compartments. A recent report has revealed S1P epigenetic regulation of gene expression through direct intracellular interaction with histone deacetylases (HDACs) (Hait et al, 2009). Through this mechanism, perhaps increasing intracellular S1P levels alters gene expression, which ultimately leads to elevated translation of muscle proteins, such as Projectin, which then reduces muscle wasting.…”
Section: Discussionmentioning
confidence: 99%
“…Though flies do have G protein-coupled receptors, they do not appear to have the S1P receptors seen in vertebrates, suggesting that S1P receptor-mediated signaling might have evolved later in higher organisms. S1P lyase mutants increase intracellular S1P levels (Ikeda et al, 2004) and S1P is generated and has been shown to function inside the cells (Hait et al, 2009;Breslow and Weissman, 2010;Strub et al, 2010;Yonamine et al, 2011), indicating that the suppression of muscle wasting in Drosophila occurs intracellularly. With this in mind, we hypothesized that if spinster, like its mammalian homolog spns2, were an S1P transporter its reduction would prevent S1P from leaving the cytoplasmic compartment and it would then behave like reduced Sply and suppress muscle wasting.…”
Section: Discussionmentioning
confidence: 99%
“…We distinguished four fractions: (1) medium surrounding the cells, (2) cytosol, (3) nucleus and (4) the membranous compartments. Because the major FTY720 bio-activating enzyme SphK2 is located primarily in the nuclear and membranous compartments (Igarashi et al, 2003;Hait et al, 2009) we were interested to analyze how FTY720 and FTY720-P are distributed not only in wild type mice, but also in the splenocytes deficient for SphK2. Furthermore, our concern was to determine whether the distribution of FTY720 and FTY720-P is affected in the absence of the enzyme SphK1, phosphorylating S1P extranuclearly.…”
Section: Discussionmentioning
confidence: 99%
“…At steady state, levels of these biosynthetic intermediates are quite low, but they can be rapidly produced during signal transduction via de novo synthesis or breakdown of mature sphingolipids. Identifying the effectors of signaling sphingolipids is an area of ongoing research, with recent studies showing that intracellular targets include histone deacetylases (Hait et al 2009), Bcl-2 family proteins (Chipuk et al 2012), the ubiquitin ligase Traf2 , and kinases and phosphatases (for review, see Hannun and Obeid 2008). One of the best-characterized modes of sphingolipid signaling is seen for sphingosine-1-phosphate (S1P), which is an agonist for the G protein-coupled receptors (GPCRs) encoded by S1PR1-5 (for review, see Blaho and Hla 2011).…”
Section: Sphingolipid Modes Of Actionmentioning
confidence: 99%